Area Wide Road User Charging in Denmark - Kildebogaard, Jan (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
Danish cities are facing increasing traffic volumes resulting in congestion and environmental problems. Vehicle and fuel taxes are already high and it is not considered politically feasible to raise them further. Consequently, there has been certain political interest in a general road pricing solution as a demand management tool. A research programme has been launched focusing on analysing the economic, technical and behavioural impacts of a countrywide distance-based road pricing system. The concept of such a system has been defined based on a set of user requirements of which fairness and privacy are high ranked issues. The user acceptance and behavioural response to the system is being investigated in interviews and questionnaires and the overall effect on traffic will be estimated through model calculations. Ideally, the results of the programme will form the basis for future political decisions with regard to road user charging.